Optimal Feedback Switching Control Design for the Turbocharged Diesel Engine with an EGR System - Gokhale, Shashidhar S; Kulkarni, S. Patil; Yathisha, L (International Journal of Computer Sciences and Engineering, 2025)
In the present scenario the optimization of engine parameters is very much necessary for the smooth operation of automotive engines. Switching among various strcutures is an essential feature in many engineering applications such as power systems, aircraft systems, etc. This paper presents the intelligent switching technique for the two optimized feedback controllers of the exhaust gas recirculation (EGR) system. The proposed switching control is investigated for the linearized state space model of turbocharged diesel engine with an EGR system. The results are compared with individual feedback structure as well as switching techniques to select the best controller for the future direction